DAMPAK VARIABILITAS IKLIM MUSIMAN PADA PRODUKSI PADI SAWAH TADAH HUJAN DI PULAU LOMBOK (IMPACT OF INTERANNUAL CLIMATE VARIABILITY ON RAINFED PADDY PRODUCTION IN LOMBOK ISLAND) - I. Yasin; M. Ma'shum (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2006)
Variability of inter-anuual rainfall has great impact on agricultural production. The inter-annual rainfall variability mainly causes cropping and harvest failure in rainfed land due to drought and flood. Although the onset of season is usully known, the characteristic of in coming rainfall is usually not predictable. Thus the understanding of the cause of rainfall variability may lead to establishment of new system to forecast seasonal rainfall characteristics. The aims of this research are to study water availibity for dry direct seeding rice by considering water balance in southern Lombok and understanding the relationship between ENSO phenomena with rain event in Lombok as well using SOI for predicting seasonal rainfall events. The results of this research showed that average rainfall in southern Lombok is 1450 mm with 950 mm the lowest and 2460 the highest. Southern Lombok has three water surplus months (with rainfall >200 mm), and 5 to 6 water deficit months (with less than 100 mm rainfall).. Inter annual rainfall variation is closely correlated to ENSO phenomena where the rainfall tend to be obove normal in La Niña years and below normal in El Niño years. The short term wet months and wide range of rainfall varibility lead to the need to establishment of water storage system and the application of water and cropping management which suitable to rainfall characteristics and local environmental conditions. The use of ENSO and SOI value to forecast seasonal rain events may be suitable and may reduce the risks of cropping system in rainfed agricultural land.